The complete general secretory pathway in gram-negative bacteria. - Pugsley, A P (1993)
The unifying feature of all proteins that are transported out of the cytoplasm of gram-negative bacteria by the general secretory pathway (GSP) is the presence of a long stretch of predominantly hydrophobic amino acids, the signal sequence. The interaction between signal sequence-bearing proteins and the cytoplasmic membrane may be a spontaneous event driven by the electrochemical energy potential across the cytoplasmic membrane, leading to membrane integration. The translocation of large, hydrophilic polypeptide segments to the periplasmic side of this membrane almost always requires at least six different proteins encoded by the sec genes and is dependent on both ATP hydrolysis and the electrochemical energy potential. Signal peptidases process precursors with a single, amino-terminal signal sequence, allowing them to be released into the periplasm, where they may remain or whence they may be inserted into the outer membrane. Selected proteins may also be transported across this membrane for assembly into cell surface appendages or for release into the extracellular medium. Many bacteria secrete a variety of structurally different proteins by a common pathway, referred to here as the main terminal branch of the GSP. This recently discovered branch pathway comprises at least 14 gene products. Other, simpler terminal branches of the GSP are also used by gram-negative bacteria to secrete a more limited range of extracellular proteins.